Reliability of Web-Based Information in Inquiry Projects - Correa, Andre Luis [UNESP]; Lacerda Rabello, Cintia Regina; Okada, Alexandra (Springer, 2014)
This case study aims at identifying how a community of secondary school students selects web-based information and factors associated with the reliability of online reference sources during their collaborative inquiry (co-inquiry) projects. This study, conducted in a public secondary school in Brazil, focused on information literacy skills for collaborative open learning (colearning). The research is based on qualitative content analysis implemented on the online platform weSPOT. Although students are mindful of the importance of comparing different sources of information they seem not to be aware of reliability in online environments. Teacher's guidance is essential to support co-learners in developing competences, particularly related to critical thinking.
Keywords: Secondary school information literacy; co-inquiry; weSPOT